Evaluation of the anti-resorptive ability of an experimental acetazolamide paste for the treatment of late replanted teeth: A study in rats - Mori, Graziela Garrido [UNESP]; Poi, Wilson Roberto [UNESP]; Castilho, Lithiene Ribeiro [UNESP] (Wiley, 2013)
When late replantation is performed, the root surface and root canal should be treated. Notwithstanding failures still occur, because of the high rates of root resorption, evidencing the need to search for substances that may inhibit root resorption. The acetazolamide is a known anti-resorptive agent, and its use as root canal dressing may increase the success rates in the treatment of root resorption. Therefore, this study evaluated the effect of an acetazolamide paste used as root canal dressing in late replanted teeth. The study was conducted on 24 maxillary right incisors of rats, which were avulsed and divided in two groups. In group I, the teeth were kept dry for 30min, had their root surfaces rubbed with a blade, and were treated with 2% sodium fluoride at pH 5.5 for 20min; the root canals were instrumented and filled with acetazolamide paste; and then the teeth were replanted. In group II, the treatment was similar to group I, except for the root canal dressing, with utilization of calcium hydroxide in group II. At 15 and 60days after replantation, the animals were killed and the specimens were processed in a histotechnical laboratory for microscopic and morphometric analysis. The results demonstrated the ability of both intracanal substances to limit root resorption, yet they were unable to completely inhibit the root resorption. Replacement resorption lacunae were present in greater proportion in group II, at 60days. It was concluded that the acetazolamide paste was effective to limit the root resorption, being more effective in limiting the replacement resorption compared with calcium hydroxide. © 2012 John Wiley & Sons A/S.
Keywords: Acetazolamide; Avulsion; Root resorption